Derivational suffixes: A review of denominal adjectives in English language learning - Musdaliffa Musdaliffa; Siska Bochari; Maf'ulah Maf'ulah; Darmawan Darmawan (Celtic : A Journal of Culture, English Language Teaching, Literature and Linguistics, 2026)
This study intended to investigate the difficulties encountered by EFL learners in using four derivational adjective-noun suffixes (-al, -ous, -ic, and -ful) and their factors. Although derivational morphology can contribute to vocabulary development and academic skills, the use of suffixes that form adjectives is still a difficulty for many EFL learners. This research used a non-experimental quantitative descriptive method. The population and sample for this study comprised 33 students in the fifth semester of the Morphology course in the English Education Study Program. Data were collected using a test and a questionnaire to assess conditions influencing students' abilities. Test results showed that the four endings varied in difficulty. The endings -ous and -ic were the most difficult for students to use correctly, while -al was the easiest. Student use of -ful was not entirely principled. However, the level of accuracy for the base noun seemed to be a defining factor in suffix use accuracy. The results of the questionnaire also showed that a lack of morphological awareness, limited vocabulary size and pedagogical limitations were the three primary variables influencing students' capacity to generate adjectives. There was no appreciable impact from other factors such L1 interference, overgeneralization, lack of productive practice, and limited exposure to authentic texts. These results emphasize the need to provide more direct instruction in derivational morphology, broaden the range of activities, and increase exposure to scholarly terminology. Improvements in these areas may improve students' understanding of morphology and enable them to produce more accurate and complex academic language.